Effect of glutamic acid on the preparation and characterization of Pickering emulsions stabilized by zein. (1st January 2022) - Song, Teng; Xiong, Zhiyu; Shi, Tong; Yuan, Li; Gao, Ruichang
Graphical abstract: Highlights: Glutamic acid promoted the aggregation of zein. The secondary structure of zein changed by the addition of glutamic acid. Glutamic acid promoted the adsorption of zein on the surface of oil droplets. Hydrophobic and electrostatic interaction were the main driving force of ZCPs. Abstract: In this study, glutamic acid and zein were utilized to prepare colloidal nanoparticles as stabilizers for Pickering emulsions. The effect of the ratio of glutamic acid to zein on the stability, zeta potential, particle size, morphology, and structure of colloidal nanoparticles was studied. The results showed that zein and glutamic acid combined in the form of noncovalent bonds, which changed the characteristics of the zein. In addition, colloidal particles aggregation was induced by glutamic acid, which altered the distribution of droplets in the emulsion, and increased the adsorption of proteins on the surface of the oil droplets, as reflected by the analysis of the size, microstructure, rheological behaviours, and driving force of the Pickering emulsion. Hydrophobic interactions and electrostatic interactions were the main driving forces for the formation of colloidal particles, which was determined by driving force analysis and the change of the zeta potential.